The Common Hurdles of Flipped Learning Approach - Abd Rahman, Siti Fatimah; Hashim, Harwati; Md Yunus, Melor; Mohd Ali, Siti Farhani (Human Resource Management Academic Research Society, 2021)
This paper provides a review of the past studies related to flipped learning as well as the hurdles faced by educators in integrating the flipped learning approach. Even though flipped learning has many benefits, and it has been proven to enhance learners’ achievement by a number of studies, challenges in implementing it still need to be endured by educators. The highlighted hurdles are the negative perception, the development of the digital instructions, accessibility, educator and learner’s resistance, lack of learner responsibility, workloads and traditional classroom. Those hurdles might lead to educators’ resistance in implementing flipped learning approach. However, educators need to come out with strategies in overcoming the issues.